Burkina Faso : Staff Report for the 2003 Article IV Consultation and Request for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2003)
This paper assesses Burkina Faso's 2003 Article IV Consultation and a Request for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Burkina Faso's performance under PRGF-supported programs during 1993-2002 and in implementing the policy agenda laid out in the Poverty Reduction Strategy Paper adopted in 2000 was satisfactory. Real GDP recovered strongly, and inflation remained low. The economic, financial, and social situation remains fragile and difficult. The IMF staff has supported the government structural reform strategy aimed at promoting good governance, economic diversification, competitiveness, and private sector development.